2017
DOI: 10.1111/jvim.14646
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low‐dose (2 millicurie) versus Standard‐dose (4 millicurie) Radioiodine Treatment for Cats with Mild‐to‐Moderate Hyperthyroidism

Abstract: BackgroundRadioiodine (131I) is effective treatment for hyperthyroidism in cats, but optimal dose to restore euthyroidism without inducing hypothyroidism is unclear. Treatment‐induced hypothyroidism can lead to azotemia and reduced duration of survival.ObjectiveTo compare efficacy and short‐term outcomes of low‐dose 131I versus higher, standard‐dose 131I as treatment for hyperthyroidism.AnimalsA total of 189 client‐owned cats undergoing 131I treatment for mild‐to‐moderate hyperthyroidism (serum T4 ≥ 4.0 μg/dL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
128
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(140 citation statements)
references
References 43 publications
(106 reference statements)
8
128
1
3
Order By: Relevance
“…Only 5 (1.9%) cats developed overt hypothyroidism (low T 4 with high TSH concentration), resulting in a much lower prevalence of overt hypothyroidism than that reported after administration of higher 131 I doses . The prevalence of subclinical and overt hypothyroidism in the cats of this study is similar to those that we have previously reported in other cats treated with low‐dose 131 I …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Only 5 (1.9%) cats developed overt hypothyroidism (low T 4 with high TSH concentration), resulting in a much lower prevalence of overt hypothyroidism than that reported after administration of higher 131 I doses . The prevalence of subclinical and overt hypothyroidism in the cats of this study is similar to those that we have previously reported in other cats treated with low‐dose 131 I …”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the proportion of cats that develop azotemia after treatment for hyperthyroidism depends, at least in part, on the degree to which the hyperthyroidism is controlled (ie, how low the serum T 4 falls) . Importantly, azotemia is more likely to develop in cats with overt hypothyroidism than in cats with subclinical hypothyroidism or in 131 I‐treated cats that become euthyroid . As in previous studies, these cats with overt hypothyroidism had a higher prevalence of azotemia (80%) than did the cats with milder, subclinical hypothyroidism (31%).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is important to note that a higher cut‐off for TSH to define overt hypothyroidism was used compared to our current report (0.3 versus 0.15 ng/mL) (Lucy et al . ). In the same previous study, the incidence of subclinical hypothyroidism was 46% in cats treated with standard dose RAI and 21% in cats treated with low‐dose RAI.…”
Section: Discussionmentioning
confidence: 97%